Cold War on CNN, Part 9: The Wall 1958-1963 (Jeremy Isaacs Productions, 1998)
For years, West Berlin was an escape route for East Germans seeking to flee communism. But growing Cold War tensions forced the Soviet bloc to erect a deadly blockade across the city -- a Wall that divided Berlin for nearly three decades.